In silico study of the essential oil compounds of ginger and thyme on Coronavirus-2 receptors - Caroline, Caroline; Ervina, Martha; Pratama, Muhammad Rizki Fadhil; Jessica, Maria Anabella (Pharmaciana, 2023)
Coronavirus-2 (SARS-Cov-2) is a virus that attacks the respiratory system and causes the Covid-19 pandemic. After the pandemic, prevention and appropriate therapy research continue to be carried out to anticipate the emergence of more dangerous viruses. In line with the culture of consuming herbs that has arisen due to the effects of the pandemic, in this study, an insilico screening was carried out for essential oil compounds produced by ginger and thyme herbs which have been widely consumed by the public. The aim of the research was to find the essential oil content that has the most potential as an antiviral against coronavirus-2. The research method was carried out in silico, including ligand preparation, receptor and method validation, and analysis of ligand-receptor binding interactions using the AutoDoc 4.2.6 program. As a comparison, a study was conducted on remdesivir and favipiravir, which have been used as antivirals. The three components that have the most potential based on the calculation of the free energy value, were determined by the ADMET parameters using the Admet lab 2.0 program. The results showed that the three components in the essential oil exhibited better interactions when compared to remdesivir and favipiravir at the 3-Cl protease and spike glycoprotein receptors. The results of the insilico study and ADMET prediction test showed that of the three most potent compounds, lamda-farnesen was the most potent and safe to use